Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2007)
Glaucoma progression is associated with decreased blood flow velocities in the short posterior ciliary artery Zeitz O, Galambos P, Wagenfeld L, Wiermann A, Wlodarsch P, Praga R, Matthiessen E T, Richard G, Klemm M Br J Ophthalmol 2006;90:1245-8. Surgical embolus removal in retinal artery occlusion Garcia-Arumf JG, Martinez-Castilio V, Boixadera A, Fonoliosa A, Corcostegui B Br J Ophthalmol 2006; 90: 1252-5. Bilateral cataract surgery and driving performance Wood JM, Carberry TP Br J Ophthalmol 2006; 90:1277-80. Insights into the age-related decline in the amplitude of accommodation of the human lens using a nonlinear finite-element model Schachar RA, Abolmaali A, Le T Br J Ophthalmol 2006; 90: 1304-9. Acute Endophthalmltis in Eyes Treated Prophylactically with Gatifloxacin and Moxifloxacin Deramo VA, Lai JC, Fastenberg DM, Udell IJ Am J Ophthalmol 2006; 142: 721-5. Atopic Disease and Herpes Simplex Eye Disease: A Population-Based Case-Control Study Prabriputaloong T, Margolis TP, Lietman TM, Wong IG, Mather R, Gritz DC Am J Ophthalmol 2006; 142: 745-9. Wavefront Analysis and Contrast Sensitivity of Aspheric and Spherical Intraocular Lenses: A Randomized Prospective Study Rocha KM, Soriano ES, Chalita MR, Yamada AC, Bottos K, Bottos J, Morimoto L, Nose W Am J Ophthalmol 2006; 142:750-6.